Surface Plasmon-Polariton: A Novel Way To Initiate Azide–Alkyne Cycloaddition; Langmuir; Vol. 35 (6) - Guselnikova O. A. Olga Andreevna; Postnikov P. S. Pavel Sergeevich; Chehimi M. M. Mohamed; Kalachyova E. Evgeniya; Svorcik V. Vaclav; Lyutakov O. Oleksy (2019, 2019)
Title screen